2010
DOI: 10.1002/rem.20265
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of DDT‐contaminated soil using optimized mixtures of surfactants and a mixing system

Abstract: Soil contaminated with persistent pesticides, such as DDT, poses a serious risk to humans and to wildlife. A surfactant-aided soil-washing technique was studied as an alternative method for remediation of DDT-contaminated soil. An ex situ soil washing method was investigated using nonionic and anionic surfactants due to the clayey structure of the contaminated soil. A mixture of 1 percent nonionic surfactant (Brij 35) and 1 percent anionic surfactant (SDBS) removed more than 50 percent of DDT from soil in a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The desirable characteristics of a surfactant in sediment washing are the following: biodegradable and soluble at ambient temperature at the time of sediment processing, low toxicity, low sorption to sediment, low surface tension, and low cmc level. Ghazali et al [42] reported that a mixture of Brij 35, a nonionic surfactant, and sodium dodecyl benzene sulfonate, an anionic surfactant, was more effective than individual surfactants in removing DDTR. Wash-off liquids containing DDTR are treated (dechlorinated) in the next step using different methods, such as degradation using zero-valent iron under anaerobic conditions [86], reduci n g a g e n t s ( c y s t e i n e o r s o d i u m s u l f i d e ) , o r photodechlorination reaction [19].…”
Section: Sediment Washingmentioning
confidence: 99%
“…The desirable characteristics of a surfactant in sediment washing are the following: biodegradable and soluble at ambient temperature at the time of sediment processing, low toxicity, low sorption to sediment, low surface tension, and low cmc level. Ghazali et al [42] reported that a mixture of Brij 35, a nonionic surfactant, and sodium dodecyl benzene sulfonate, an anionic surfactant, was more effective than individual surfactants in removing DDTR. Wash-off liquids containing DDTR are treated (dechlorinated) in the next step using different methods, such as degradation using zero-valent iron under anaerobic conditions [86], reduci n g a g e n t s ( c y s t e i n e o r s o d i u m s u l f i d e ) , o r photodechlorination reaction [19].…”
Section: Sediment Washingmentioning
confidence: 99%
“…Wenzel et al (2002) and Sun et al (2009) found that soils with a higher organic fraction would bind more DDT. However, others have reported that clays could have a major influence on sorption (Dai et al 2008;Ghazali et al 2010).…”
Section: Sorption and Desorption With Conventional 24 H Time Stepmentioning
confidence: 97%
“…Aged activated carbon sorbed up to 10 % more than freshly spiked carbons (Oen et al 2011). Soil parameters affecting desorption of DDT were stated to be % organic matter, amount of dissolved organic carbon, surface area, % clay/silt, and pH levels (Ghazali et al 2010;Holoubek et al 2009;Oen et al 2011;Thangavadivel et al 2011). For instance, relatively low pH values (pH=5.4) were said to cause stronger hydrogen bonding when compared to neutral or alkali pH conditions (Boivin et al 2005;Thangavadivel et al 2011).…”
Section: Desorption Of Aged Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…DDT is associated with serious risks to the environment and human health, including carcinogenesis, endocrine disruption, and estrogenic action. , However, DDT and its metabolites (DDXs), particularly dichlorodiphenyldichloroethane (DDD) and dichlorodiphenyldichloroethylene (DDE), which could be the congeneric impurities of technical DDT at very low amounts, are still frequently worldwide detectable in considerable amounts even decades after the DDT prohibition . Those metabolites are also reported to be environmentally and biologically harmful. The ongoing usage of the DDT related pesticide dicofol, as well as specialty applications of DDT in antifouling paints and limited disease vector control efforts, result in substantial emission of DDT/DDXs that are cause for continued environmental concern. , Consequently, knowledge on nonextractable DDXs is still necessary for both risk assessment and remediation actions.…”
Section: Introductionmentioning
confidence: 99%